2013
DOI: 10.1523/jneurosci.2921-12.2013
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Localization of Cav2.1 (P/Q-Type) Voltage-Dependent Calcium Channels in Purkinje Cells: Somatodendritic Gradient and Distinct Somatic Coclustering with Calcium-Activated Potassium Channels

Abstract: P/Q-type voltage-dependent calcium channels play key roles in transmitter release, integration of dendritic signals, generation of dendritic spikes, and gene expression. High intracellular calcium concentration transient produced by these channels is restricted to tens to hundreds of nanometers from the channels. Therefore, precise localization of these channels along the plasma membrane was long sought to decipher how each neuronal cell function is controlled. Here, we analyzed the distribution of Cav2.1 subu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

21
135
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(159 citation statements)
references
References 68 publications
(95 reference statements)
21
135
1
Order By: Relevance
“…Because VGluT1 is selectively expressed in PF boutons in the molecular layer (43), these results confirm that these profiles originate from PF-MLI synapses. We also found that the presynaptic P-face of these synapses was flat, in contrast to the concave profile observed at PF-PC synapses (33); this difference provides an additional criterium to distinguish between PF-MLI and PF-PC synapses. Finally, we occasionally found GABAergic synapses on MLIs by double labeling for AZ proteins and VGAT (Fig.…”
Section: Identification Of Pf-mli Synapses In Sds-digested Freeze-framentioning
confidence: 52%
See 1 more Smart Citation
“…Because VGluT1 is selectively expressed in PF boutons in the molecular layer (43), these results confirm that these profiles originate from PF-MLI synapses. We also found that the presynaptic P-face of these synapses was flat, in contrast to the concave profile observed at PF-PC synapses (33); this difference provides an additional criterium to distinguish between PF-MLI and PF-PC synapses. Finally, we occasionally found GABAergic synapses on MLIs by double labeling for AZ proteins and VGAT (Fig.…”
Section: Identification Of Pf-mli Synapses In Sds-digested Freeze-framentioning
confidence: 52%
“…Assuming that receptor density remains constant, as suggested by the finding of very high and homogenous AMPA receptor density at PF-MLI synapses (37) (30,31,33), we found that Ca v 2.1 channel labels were not distributed uniformly. The distribution of distances between any pair of particles within an AZ displayed a peak in the range between 0 nm and 50 nm (particularly evident in 4-wk data), indicating particle association within clusters, whereas beyond this range particle distances were distributed broadly ( Fig.…”
Section: Identification Of Pf-mli Synapses In Sds-digested Freeze-framentioning
confidence: 57%
“…At typical synapses, docking and fusion take place at structurally specialized regions along the PM called active zones (9,10). Several lines of evidence suggest that the formation of the SNARE core complex occurs in the macromolecules composing the common active zone organelle, active zone material (AZM) (2,(11)(12)(13)(14), which is positioned near Ca 2+ channels concentrated in the PM at active zones (15)(16)(17). Influx of Ca 2+ through the channels after the arrival of a nerve impulse triggers fusion of the VM of docked SVs with the PM.…”
mentioning
confidence: 99%
“…Unlike in the hippocampus, postsynaptic Ca 2+ signaling at PF-PC spines may not be dominated by ionotropic glutamatergic receptors, as postsynaptic N-methyl-D-aspartate receptors (NMDARs) are not prominently present at this site and AMPA receptors are predominantly impermeable for calcium ions (4,5). PCs bear different voltage-dependent Ca channels including P/Q-type (6)(7)(8) and T-type channels (9,10). The spines of PCs contain a high density of Ca V 3.1 T-type channels (11), which can be readily activated by typical bursts of PF activity that occur during sensory stimulation (12)(13)(14).…”
mentioning
confidence: 99%